Respostas

2014-08-14T18:53:04-03:00
A) 2 -  2x = 7 - 3x
    -2x + 3x = 7 - 2
      x = 5

b)12+2(y+4)=50-16 
    12 + 2y + 8 = 34
    20 + 2y = 34
    2y = 34 - 20
   2y =  14
   y = 14/2
   y = 7

c) -9 + 3y - 1 = y + 7
    -10 + 3y = y + 7
     3y - y = 7 + 10
     2y = 17
/     y = 17/2
      y = 8,5
  • Usuário do Brainly
2014-08-14T18:53:54-03:00
A) Temos que, 2-2x=7-3x. Assim, 3x-2x=7-2, ou seja, x=5

b) Do enunciado, 12+2\cdot(y+4)=50-16. Deste modo, 2y+8+12=34.

Assim, 2y+20=34/tex], isto é, [tex]2y=14/tex] e, portanto, [tex]y=\dfrac{14}{2}=7

c) Temos x-3x+5=1-x. Assim, x-3x+x=1-5, ou seja, -x=-4.

Logo, x=4.

d) Como -9+3y-1=y+7, temos 3y-y=7+9+1, isto é, 2y=17.

Com isso, y=\dfrac{17}{2}